Internet memes with feminist content as a communication media of philosophical meaning through building a deep understandings on women’s positions - Ariani, Iva; Rachmadani, Fadhila (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research departs from interest and curiosity about women's issues and positions as represented in internet memes. The purpose of this research is to uncover the hidden philosophical meaning behind internet memes with feminist themes, chosen using a purposive sampling technique. This research thus provides a feminist internet meme analysis using the theoretical framework of critical discourse Sara Mills. This qualitative research is divided into four sections, after opening with an overview of internet memes, their philosophical background, and Sara Mills critical discourse to looking at the issue of women's positions. The first section discusses internet memes with a Western cultural background; the second section the analysis of internet memes with an Eastern cultural background; and the third section argues the analysis of internet memes with a background in Islamic culture. The fourth section will provide a philosophical reflection on feminist as reflected in internet memes from Western, Eastern and Islamic cultures as viewed from critical discourse Sara Mills. The research seeks the philosophical meaning of internet memes with feminist themes by using a Sara Mills critical discourse framework. This approach will offer a deep understanding of women’s positions within their cultural backgrounds, as depicted through internet memes to communicate the philosophical meaning of feminist issues.